Native and alien flower visitors differ in partner fidelity and network integration - Trøjelsgaard, Kristian; Heleno, Ruben; Traveset, Anna; Mayfield, Margaret (Ecology letters, 2019)
Globalisation persistently fuels the establishment of non‐native species outside their natural ranges. While alien plants have been intensively studied, little is known about alien flower visitors, and especially, how they integrate into natural communities. Here, we focus on mutualistic networks from five Galápagos islands to quantify whether alien and native flower visitors differ consistently in their pairwise interactions. We find that (1) alien flower visitors have more interaction partners and larger species strengths (i.e. plants are more connected to alien insects), (2) native insects tend to have higher partner fidelity as they deviate more from random partner utilisation, and iii) the difference between native and alien flower visitors in network integration intensifies with island degradation. Thus, native and alien flower visitors are not interchangeable, and alien establishment might have yet unforeseen consequences for the pairwise dynamics between plants and flower visitors on the Galápagos – especially on the heavily disturbed islands.